Digital microfluidics platform for interfacing solid–liquid extraction column with portable capillary electropherograph for analysis of soil amino acids. Issue 3 (26th October 2015) - Gorbatsova, Jelena; Jaanus, Martin; Vaher, Merike; Kaljurand, Mihkel
Abstract : In this work, the concept of a field‐portable analyzer is proposed that operates with milliliter amounts of solvents and samples. The need to develop such an analyzer is not only driven by specific extraterrestrial analysis but also, for example, by forensics applications where the amount of liquid that can be taken to the field is severely limited. The prototype of the proposed analyzer consists of a solid–liquid extractor, the output of which is connected to the micropump, which delivers droplets of extracts to digital microfluidic platform (DMFP). In this way, world‐to‐chip interfacing is established. Further, the sample droplets are transported to CE capillary inlet port, separated and detected via a contactless conductivity detector. Working buffers and other solvents needed to perform CE analysis are also delivered as droplets to the DMFP and transported through the CE capillary. The performance of the analyzer is demonstrated by analysis of amino acids in sand matrices. The recovery of the spiked amino acids from the inert sand sample was from 34 to 51% with analysis LOD from 0.2 to 0.6 ppm and migration time RSD from 0.2 to 6.0%.